SEMANGAT KEBANGSAAN KAUM RELIGIUS KATOLIK SEBAGAI UPAYA KONTRA-RADIKALISME AGAMA DI MASYARAKAT PLURAL KOTA PONTIANAK - Maria Magdalena Husun; Yanto Sandy Tjang; Amandus Suhaedi Dol; Felisitas Yuswanto (IN VERITATE LUX, 2026)
Religious radicalism is a multidimensional phenomenon arising from the complex interaction of theological, social, political, economic, and educational factors. In pluralistic societies such as Pontianak, radicalism has the potential to disrupt social cohesion if not addressed through a comprehensive approach that integrates faith, ethics, and social practice. This study aims to analyze how Catholic monks and nuns internalize and actualize the spirit of nationalism as a counter-radicalism strategy, while also understanding the meaning of Church teachings in the context of diversity, democracy, and respect for human dignity. Using a qualitative approach, data were collected through in-depth interviews with religious figures across several parishes of the Archdiocese of Pontianak and analyzed thematically. The findings indicate that radicalism prevention is carried out through enlightening Catholic religious education, interfaith dialogue, the reinforcement of tolerance values, respect for human dignity, development of critical thinking, and active engagement in diverse communities. The implementation of the spirit of nationalism not only strengthens loyalty to the state but also affirms the Gospel’s call to live in fraternity, solidarity, and justice. Accordingly, monks and nuns serve as agents of social transformation, embodying Gospel values while enhancing cohesion and peace in pluralistic societies.